Perceived organizational support (POS), organizational commitment and turnover intentions amongst employees in Malaysian Banking Industry - Lagaa, Suhail Abdulazizi Mahmoud; Siam, Mohammed R A; AWN, Abdullah Mohammed Ali Ammar (2017)
Employee turnover is considered to be an ongoing problem in different organizations.This goes a long way to disturb the growth, productivity and increases the cost of organization by recruiting new employees and causes sharing of knowledge.In fact, retaining of talent is now becoming more critical in the world where the human capabilities of an organization are vital source of competitive advantage.To control employee turnover, this study tried to develop a linkage between Perceived Organizational Support (POS) and Organizational Commitment.Therefore, the ultimate objective of this study is to investigate the impact of Perceived Organizational Support (POS) and Organizational Commitment on Turnover Intention. To achieve this objective, four hypotheses are proposed concerning the relationship of Perceived Organizational Support (POS) and Organizational Commitment (i.e., affective commitment, continuous commitment, normative commitment) with Turnover Intention. Data was collected through 5-point likert scale and 300-questionnaires were distributed among the employees of bank by using convenience sampling.The data was analyzed using SPSS version 22.Results of the study revealed that significant negative relationship exists between Perceived Organizational Support (POS), Organizational Commitment and Turnover Intentions among the employees.Hence, this study is contributing in the body of knowledge by exploring a linkage between Perceived Organizational Support (POS) and Organizational Commitment to enhance employee retention and tried to resolve the important issue of Turnover Intention by developing a framework. This study is more significant for practitioners to control employee turnover by exercising good practices of Perceived Organizational Support (POS) and Organizational Commitment.